Analysis of risk factors in the development of bronchopleural fistula after major anatomic lung resection: experience of a single centre. Issue 4 (1st February 2017) - Nachira, Dania; Chiappetta, Marco; Fuso, Leonello; Varone, Francesco; Leli, Ilaria; Congedo, Maria T.; Margaritora, Stefano; Granone, Pierluigi
Abstract : Background: The bronchopleural fistula (BPF) is a rare but potentially fatal complication of major thoracic surgery. The purpose of this work is to investigate the risk factors associated with the development of fistulas after lobectomy and pneumonectomy. Methods: We retrospectively reviewed the records of 835 patients who underwent major anatomic lung resection at our centre from January 2003 to December 2013. Of these, 49 underwent pneumonectomy (P group) and 786 lobectomy (L group). Results: A total of 18 patients (2.6%) developed a BPF in the postoperative period, of which there were 11 in the L group (1.3%) and seven in the P group (14.28%). The 30‐day mortality was 0.05% (one patient after right pneumonectomy). In the L group, three patients developed a fistula after a left lobectomy and eight after a right one, of which four developed after bilobectomy. Univariate analysis showed that induction therapy, lower lobectomy, manual suture of the bronchus, 'not covered' bronchial stump, empyema, postoperative anaemia and pulmonary infections and mechanical ventilation >24 h are associated with the development of fistulas after lobectomy. Multivariate analysis confirmed that induction therapy, manual closure of the bronchus, postoperative pulmonary infections and anaemia are the main risk factors involved in our series. In the P group, four patients developed a fistula after a right pneumonectomy and three after a left one. Postoperative empyema and pulmonary infections, mechanical ventilation >24 h and female gender emerged as the main risk factors on univariate analysis, while on multivariate analysis, only the female gender presented a trend towards significance. Conclusions: Postoperative pulmonary infections, empyema and mechanical ventilation >24 h are strongly associated with the development of BPFs after both pneumonectomy and lobectomy in our series.